(untitled) (Research, Society and Development, 2022)
This study aims to associate exploratory variables of nurses to the CAP survey, to assess the knowledge, attitude and practice of nurses working in Family Health Strategies about the prevention and treatment of leprosy. The research will have as a cross-sectional, analytical study method of the CAP type (Knowledge, Attitude and Practice), with a quantitative approach. To be carried out with 18 coordinator nurses responsible for the Basic Health Unit, of the primary care network. The study instrument will undergo face validation by a committee of judges, where it will be applied after obtaining a validation of 0.90, the questionnaire consists of open and closed questions. The data will pass through the statistical program Statistical Package for the Social Sciences (SPSS) version 20.0, and Pearson’s chi-square test (X²) to verify the existence of an association between the dependent and independent variables, with p value < 0, 05 significant. The project was submitted to the research ethics committee. It includes analyzing whether nurses can identify problems and plan actions through practice in order to interrupt the chain of transmission, helping to eradicate the Leprosy.